Depressive and anxiety disorders in high school students (Research, Society and Development, 2023)
Depression and anxiety are neglected pathologies in adolescence by society, however they are one of the biggest mental health problems in the world. Adolescents, in most cases, adopt a defensive behavior with a tendency to isolation, making early diagnosis and prognosis of the disease difficult. Thus, the aim of this study is to explore the factors associated with depression and anxiety in high school students. This is an integrative literature review, so a search was carried out on the CAPES Portal de Periódicos between February and March 2023. Six articles were included for the integrative review. The prevalence of disorders is higher in women due to subjective symptomatology, for example, excessive concerns about the body and popularity. While in men, the manifestations are excessive use of substances, aggressiveness and rebelliousness. As a risk factor for depressive symptoms is the conflicting marital relationship of the parents, absence or low level of positive aspects in family interaction and affective/family relationship. In addition, children of alcohol-dependent parents are at greater risk of developing mental disorders. Therefore, adolescents have been showing higher levels of depression and anxiety, so health professionals must be qualified and trained to identify these individuals in their clinical manifestations during consultations.